Atraumatic Technique for Removal of Lingually Placed Mandibular Teeth - Karikal, Arvind; Shetty, Tripthi P.; S., Gopinath Thilak P.; Kudthadka, Arathi (Journal of Health and Allied Sciences NU, 2021)
We describe an innovative and easy method to remove lingually placed mandibular single-rooted teeth which are not accessible to regular forceps method of extraction. This method is simple and atraumatic and preserves the lingual alveolar plate which is important for implant placement and socket perseveration. This note is aimed at highlighting a simple atraumatic technique for removal of these types of single-rooted teeth erupting on the lingual side with the help of surgical screws. This technique is more economical and considerably less cumbersome than the existing Benex system.
Keywords: atraumatic; extraction; novel technique